The Role of Strategic Foresight in Achieving the Pioneering Social Orientation : an Analytical Study of the Opinions of a Sample of University Leaders in Private Universities In the Middle Euphrates Region - Ahmed Arrak Abad (International Journal of Economics and Management Sciences, 2025)
The current study aims to determine the role of strategic foresight through its dimensions (environmental scanning capabilities, strategic choice capabilities, integration capabilities) in achieving the pioneering social orientation through its dimensions (adopting social risks, social proactivity, and social relations). This is because the research problem was represented by a number of questions that were designed to identify the intellectual frameworks of its variables, diagnose the level of interest in them in the field, and identify the appropriate procedures. The organization's main method for collecting information about the field component of the study was a questionnaire form, and the sample size was 149. By examining the link between these variables, two primary hypotheses were established, from which a number of subhypotheses were derived to gauge the degree of association and influence. With the help of (university leaders) in the subject, private universities in the Middle Euphrates region were selected for the study and testing of its theories. SPSS.V.29 The study came to a number of recommendations. Several results were reached with the program (Amos.V.26), but the most important one is that strategic foresight has a link of association and effect Moral in the social entrepreneurial orientation.